1.wykonaj mnożenie i zredukuj wyrazy podobne:
a) (x-1)(x³+x²+x+1)
b) (x+1)(x³-x²+x-1)
2.wykonaj mnożenie i zredukuj wyrazy podobne:
a)(x+7)(2x-1)
b)(2a-1)(a+4)
c)(4a-1)(2-3a)
d)(x+√5)(x-√5)
e)(2y-√3)(y+1)
f)(a+√2)(a-√3)
g)(2√2+k)(√2-k)
3.wykonaj działania:
a)(m+n)(m-2)+(m-n)(m+1)
b)(3x-2)(3x-2y+1)-4x(2x-3y+1)
c)3(m+1)(n-2)+2(n+1)(m-2)
d)x(x+1)(x+2)-x(x-1)(x-2)

liczę na szybką odpowiedź . ;)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T21:44:09+01:00
3. (m+n)(m-2)+(m-n)(m+1) = m²-2m+mn-2n + m²+m-mn-n = 2m²-m-3n

(3x-2)(3x-2y+1)-4x(2x-3y+1) = 9x²-6yx+3x-6x+4y-2 -8x²+12xy-4x= x²+6xy +4y -7x

3(m+1)(n-2)+2(n+1)(m-2) = 3mn-6m+3n-6 +2mn-4n+2m-4= 5mn-6m-4n-10

x(x+1)(x+2)-x(x-1)(x-2) = x(x²+2x+x+2)-x(x²-2x-x+2)= x³-3x²+2x -3x³+6x²-2x = 3x²

2.a)(x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
b)(2a-1)(a+4)= 2a²+8a-a-4=2a²+7a-4
c)(4a-1)(2-3a)=8a-12a²-2+3a=11a-12a²-2
d)(x+√5)(x-√5)=x²-√5x+√5x-5=x²-5
e)(2y-√3)(y+1)=2y²+2y-√3y-√3
f)(a+√2)(a-√3)=a²-√3a+√2a-√6
g)(2√2+k)(√2-k)=4-2k√2+k√2-k²=4-k√2-k²

1.a) (x-1)(x³+x²+x+1)=x⁴+x³+x²+x-x³-x²-x-1=x⁴-1
b) (x+1)(x³-x²+x-1)=x⁴-x³+x²-x+x³-x²+x-1=x⁴-1